Educação ambiental crítica: proposta de um método de ensino e aprendizagem pelas histórias em quadrinhos - (:unkn) unknown (Universidade Brasil, 2021)
Human beings interact with the environment, sometimes putting it at risk. Environmental education is shown as an alternative to alleviate this harmful situation, especially if developed through attractive and playful languages for students, such as comic books. The present dissertation - derived from qualitative and bibliographic research - aims to provide Elementary School 1 teachers with a method of teaching and learning critical environmental education based on the teacher's self-application of a standard questionnaire that enables him to critically approach environmental-themed comics with students in a more politicized and less naive way.
Keywords: Educação ambiental transformador; Ensino fundamental; Meio ambiente; CB